2018
DOI: 10.1159/000493521
|View full text |Cite
|
Sign up to set email alerts
|

Plasmapheresis Therapy in Kidney Transplant Rejection

Abstract: Kidney transplantation (KT) is considered an optimal treatment strategy for end-stage renal disease. But human leukocyte antigen-sensitized, ABO-incompatible and antibody-mediated rejection might be the alarming hurdles in KT. Therapeutic plasma exchange is the mainstay of the antibody reduction therapy for reducing autoantibody more effectively. Even in the treatment for highly sensitized patients, it has played an indispensable role. However, clinicians should tailor therapies to individual patient’s needs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…For cellular rejection, high-dose corticosteroids or lymphocyte-depleting agents are commonly used. For antibody-mediated rejection, an anti-CD20 antibody or plasmapheresis are applied [ 71 , 72 ].…”
Section: Covid-19 Vaccine Efficacy In Ckd Patients: From Ckd3-5 and Ckd-5d To Post Kidney Transplantationmentioning
confidence: 99%
“…For cellular rejection, high-dose corticosteroids or lymphocyte-depleting agents are commonly used. For antibody-mediated rejection, an anti-CD20 antibody or plasmapheresis are applied [ 71 , 72 ].…”
Section: Covid-19 Vaccine Efficacy In Ckd Patients: From Ckd3-5 and Ckd-5d To Post Kidney Transplantationmentioning
confidence: 99%
“…It is known that PP treatment is effective in antibody-mediated vascular rejection, and the nurse of the renal transplant unit is responsible for performing the technique, and should provide comprehensive assistance to the renal transplant patient. 12,13 It is specified that a study showed the role of the nurse, not only in the care of the renal transplant patient, but also as a health educator, offering adequate and effective guidelines. It is pointed out a significant concern on the part of Nursing to maintain care for the renal transplant within and outside the hospital, with guidelines that address simple and complex issues, which are of paramount importance during the pre-and post-transplant period, ensuring the success and quality of life of the transplant.…”
Section: Methods Resultsmentioning
confidence: 99%
“…Additional benefit of IVIG is its ability to replenish gamma globulin lost during therapeutic apheresis, decreasing infection risk [49].…”
Section: Ivigmentioning
confidence: 99%
“…Both immunoabsorption (IA) and plasmapheresis (PP) are known to lower HLA-specific antibody levels in a variety of clinical settings [49]. Despite the substantial reductions in the titer of donor-specific anti-HLA antibodies achieved by IA and PP, the graft survival in these patients is significantly reduced, due to rebound synthesis of de novo alloantibodies.…”
Section: Plasmapheresismentioning
confidence: 99%
See 1 more Smart Citation